Pengaruh Digital Culture Dan Perceived Organizational Support Melalui Organizational Commitment Terhadap Workforce Agility Direktorat Jenderal Bina Pemerintahan Desa Kemendagri - Jayanti, Witrin; Gustari, Irvandi; Wicaksana, Seta A. (CV ODIS, 2024)
Competent and adaptive human resources in responding to the challenges of the work environment are very important for an organization. The Directorate General of Bina Pemdes of the Ministry of Home Affairs in supporting the concept of good governance seeks to implement digital culture. However, its implementation has encountered obstacles because technology adoption and literacy depend on BPSDM and Bimtek. It can be said that the perceived organizational support of the agency is still minimal. This study aims to analyze the significant influence of digital culture on workforce agility, the significant influence of digital culture on organizational commitment, the significant influence of perceived organizational support on workforce agility, the significant influence of perceived organizational support on organizational commitment, the significant influence of organizational commitment on workforce agility, organizational commitment variables that can mediate correlational relationships Digital culture towards workforce agility and variable organizational commitment that can mediate perceived organizational support for workforce agility. The method used in this study is path analysis. The population in this study was 390 people and the sample used for the distribution of questionnaires was 263 employees of the Directorate General of Bina Pemdes. The results showed that (1 ) Digital culture did not have a significant effect on workforce agility, (2) 2) Digital culture did not have a significant effect on organizational commitment, (3) Perceived organizational support had a significant effect on workforce agility, (4) Perceived organizational support had a significant effect on organizational commitment, (5) Organizational commitment had a significant effect on the direction of positive relationships with workforce agility, (6) Digital culture mediated by organizational commitment does not have a significant effect on workforce agility, (7) Perceived organizational support mediated by organizational commitment has a significant effect on workforce agility. The conclusion in this study is that in the application of digital culture with a positive environment, agencies need to support its application from various aspects such as justice, compensation and security.